Pelatihan Pembuatan Pola Celana Santai Bagi Masyarakat Kelurahan Muaragembong Kabupaten Bekasi - Melly Prabawati; E. Lutfia Zahra (IKRA-ITH ABDIMAS, 2023)
The scope of pengabdian kepada Masyarakat (PkM) field includes the development of the welfaresector and the development of the potential of the creative industry. Activities in the PkM program carriedout by lecturers must be in accordance with the real problems and needs of the community in the PkMlocation. Skills training for making casual pants patterns is a PkM activity carried out by a lecturer inFashion Design, Faculty of Engineering, State University of Jakarta. This activity aims to provide thecommunity with knowledge and skills in making pants patterns. The community members who participatedin the skills training for making casual pants were residents of the Muaragembong sub-district, BekasiRegency. The method used in the implementation of PkM activities begins with a site survey, followed bytraining in making casual pants patterns, participants are given a module for making casual pants patterns,lecturers explain learning materials using the lecture method and demonstrate the steps for making casualpants patterns, then lecturers and students provide guidance to participants in the practice of making casualpants patterns. The involvement of students in PkM activities is so that students have a spirit of communityservice by contributing their expertise and caring about the conditions that are happening in the community.The result of PkM activities is that participants have skills in making casual pants patterns that can be sold toincrease income and can improve household welfare.